Impact tensile behavior analysis of Twaron fiber tows from fast Fourier transform. Issue 8 (April 2019) - Zhu, Lvtao; Zhu, Guocheng; Feng, Jianyong; Jin, Limin; Ma, Pibo
In this study, tensile experiments of Twaron fiber tows under different strain rates (quasi-static: 0.001 s −1, dynamic: 800–2400 s −1 ) were tested with an MTS materials tester (MTS 810.23) and a split Hopkinson tension bar, respectively. The results showed that the mechanical properties of the Twaron fiber tows were sensitive to strain rate: the stiffness and failure stress of the fiber tows increased distinctly as the strain rate increased, while the failure strain decreased. From scanning electron microscope photographs of the fracture surface, it is evident that the Twaron fiber tows failed in a tougher mode and the axial split became more severe as the strain rate increased. The tensile behaviors of the Twaron fiber tows were analyzed in the frequency domain using the fast Fourier transform method. The amplitude spectrum and power of energy absorption of the Twaron tows were concentrated in a specific frequency range and increased with strain rate.